PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, DAN UKURAN PERUSAHAAN TERHADAP KINERJA PERUSAHAAN MNUFAKTUR - Joshua Gunawan, Henryanto Wijaya (Jurnal Paradigma Akuntansi, 2020)
This study was conducted to determine the effect of managerial ownership, institutional ownership, and company size on the performance of manufacturing companies listed on the Indonesia Stock Exchange in 2015-2018. The sample selection technique used in this study uses a purposive sampling technique where the selected sample is based on various considerations and certain criteria that are tailored to the purpose of the study. Based on the specified criteria, the researchers obtained 38 manufacturing companies. The results of this study indicate managerial ownership have a positive and significant effect on company performance, institutional ownership have a positive and significant effect on company performance, and company size has a positive and not significant effect on company performance.